Mushroom identifier - Jordan, Peter (London : Sebastian Kelly, 1999)
Beginning with an explanation of everything a mushroom picker needs to know, this illustrated A-Z guide identifies the features and habitats of the most popular edible mushrooms.
Includes index.
Keywords: Mushroom identifier; v; Champignons -- Identification